Coping styles in individuals with hypertension of varying severity. (20th August 2019) - Casagrande, Maria; Boncompagni, Ilaria; Mingarelli, Alessandro; Favieri, Francesca; Forte, Giuseppe; Germanò, Rosanna; Germanò, Giuseppe; Guarino, Angela
Abstract: The strategies that people usually use to cope with stressful events, that is, their coping style, may affect blood pressure and cardiovascular functioning. Generally, hypertension is positively associated with emotion‐oriented, maladaptive coping strategies and negatively related to task‐focused coping styles, but no study has investigated the relationship between coping strategies and the severity of hypertension. This study aimed to assess whether the severity of cardiovascular disorders was associated with specific coping strategies. Participants were selected from the Policlinico Umberto I of the University of Rome "Sapienza." The sample was divided into five groups: (a) healthy people ( n = 190); (b) people with untreated hypertension ( n = 232); (c) people using antihypertensive medication ( n = 158); (d) people using antihypertensive medication with uncontrolled hypertension ( n = 179); and (e) people suffering from both hypertension and heart diseases ( N = 192). Coping strategies were evaluated with the Coping Inventory for Stressful Situations. One‐way ANCOVAs, considering Group as the independent variable and the coping strategies (task‐focused, emotion‐oriented and avoidance‐oriented coping) as dependent variables, showed that individuals affected by both hypertension and heart diseases made less use of task‐focused coping strategies than the other groups. These findings confirm the relationship between coping style and hypertension and highlight that patients with hypertension and heart diseases make less use of appropriate coping strategies.